(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The kinetics of anionic polymerization of acrylonitrile in sulphoxides (DMSO and DESO) solutions in the presence of the nitrates and chlorides of aluminium and zinc and Al(NO3)3·6DMSO complex have been investigated. It was maintained that the polymerization has anionic character. The order of reaction by initiators have been defined =0.5. It was ascertained that in first stage of reaction occurring to interaction of salts with sulphoxides, but in case of complex we have preliminary co-ordination of metal ion to sulfoxide. The interaction of water on acrylonitrile polymarization in sulfoxide solutions have been investigated too. It was shown that in case of DESO water is the only inhibitor of anionic polymerization.